ANALISIS BENTUK BENTUK PENILAIAN SIKAP SISWA SEKOLAH DASAR DI KOTA KEDIRI - Saidah, Karimatus; Damariswara, Rian (Profesi Pendidikan Dasar, 2017)
This study is aim to describe forms of attitude assessment that implemented by teacher at elementary school in Kediri. Design of this study was qualitative reseach . The subjects were teacher of elementary school that has been implementing curriculum 2013 which consist of grade 1 to grade 5 teachers.Instrument of this study was a researcher who was supported with interview guide, observation form and documentation. The finding of this study show that all of teacher write their assessment instrument similar to book teacher of curriculum 2013. Teacher use observation technique without any instrument when they do assessment. They argue that assessing attitudes using instrument is difficult and need much time.The assessment report is write using microsoftt excel application. Microsoft excel applicatioan will automatically make describtion of the student when teacher submit their assessment report.